(untitled) (Research, Society and Development, 2022)
This study aimed to identify the main forms of treatment for head and neck hemangiomas. This is an integrative literature review, whose guiding question was the therapeutic approach to hemangiomas. A bibliographic survey was carried out in the Scielo and Pubmed databases, between the years 2009 to 2019. The search resulted in the selection of 28 articles, after which the following eligibility criteria were investigated: open access, publications in Portuguese, English or Spanish and studies whose titles and abstracts were in line with the purpose of this review. At the end, 5 articles were selected. Gray literature and duplicates were excluded. Upon critical analysis of the studies, it was estimated that only 10 to 20% of hemangiomas require treatment. Therapeutic options for hemangioma are diverse, varying according to the characteristics of the patients and the peculiarities of the lesion, such as location, size, evolutionary stage and nature, arterial or venous. The treatment of minor and peripheral lesions consists mainly of sclerotherapy and surgical excision. On the other hand, larger and/or intraosseous lesions require previous embolization followed by surgical removal. There are reports of the use of drugs, such as propranolol and systemic corticosteroids, in addition to laser therapy, cryotherapy and electrocautery. Hemangiomas in the head and neck region are complex, relatively common pathologies and the therapy must be directed individually, according to the peculiarities of each case.